Histopathological changes and piscidin 5-like location in infected Larimichthys crocea with parasite Cryptocaryon irritans. Issue 99 (April 2020) - Zheng, Libing; Qiu, Jiayin; Chen, Jia; Zheng, Wei-qiang; Pan, Ying
Abstract: Cryptocaryon irritans infection could cause huge economic losses to the marine fish industry. Larimichthys crocea, a special economic species in China, suffered from the threat of serious infection, and L. crocea could enhance the level of piscidin 5-like to defense against the infection. This study set out to observe the main histopathological changes of some key tissues caused by infection, and determineed how an ectoparasite affected the expression of piscidin-5 like in its hosts. Pathological changes and immune response were assessed using histological and in situ hybridization (ISH) technologies. The infection induced inflammation occurring, especially in the gill where epithelium cells swell, hyperplasia, necrosis shedding adjacent to the parasites attachment sites. Infected hepatic cells grown big vacuoles in the cytoplasm. The boundary between red pulp and white pulp turned indistinct, splenic corpuscle lost the normal structure, the number and size of melano-macrophage centers increased apparently in the infected spleen. The whole structure of head kidney became loose. Immunostaining with RNA probes against piscidin 5-like showed subpopulations of mast cells (MCs) were positive. Piscidin 5-like-positive MCs existed mainly in the head kidney where they distributed around melano-macrophage center, followed in the gill located at different positions they also distributed in the margin of spleen, and randomly and sparsely existed in the liver. After being infected by C. irritans, the gill arch arose positive MCs groups, and they also migrated to spleen, while the positive staining deepen in other detected tissues. Therefore, organism enhanced the expression level through improving expression ability of positive MCs, or increasing the number of positive MCs. Highlights: Each tissue appeared apparent histopathological changes after being infected by Cryptocaryon irritans in Larimichthys crocea. Piscidin 5 like existed in the mast cells. Cryptocaryon irritans  infection increased the expression level of piscidin 5 like through enhancement of the mast cells expression capacity. The upregulation expression could be also reached through the increasing number of mast cells in some certain tissues.